The formation of tooth brushing automaticity of 7-8 year-old children using appreciative inquiry (Ai) approach - Lisa Prihastari; Zaura KA. Matram; Anton Rahardjo (DiscoverSys Inc., 2020)
Objective: To measure the effectiveness of the appreciative inquiry (AI) approach for the formation of tooth brushing automaticity of children in school for 2 months.Material and Methods: Randomized-Community Trial with a school-based supervised tooth brushing program for two months. Automaticity was measured with self-report behavior automaticity index (SRBAI) and intraoral examination was done with patient hygiene performance modified index (PHP-M)at the baseline, after 1 month and after 2 months. Results: automaticity proportion was significantly higher in the AI group (63.8%) compared to conventional group (22.1%) (P = 0.000; OR= 11.9, 95% CI = 4.794-29.497). Conclusion: appreciative inquiry was more effective than conventional health education approach for tooth brushing behavior change.